Roberto Juarroz y Poesía=Poesía: historia de una revista sin historia - Eraso Belalcázar, Mario (Anales de Literatura Hispanoamericana, 2010)
Little is known about Poesía=Poesía, a journal founded in 1958 by Roberto Juarroz, one of the best poets in Hispanic America in the twentieth century. In that same year appeared the first of his fourteen books, all of them entitled Poesía vertical, that have been translated into many languages around the world. With this article, I try to fill one aspect that the critical work on Juarroz has forgotten: the importance of his journal to understand his aesthetic point of view.